(untitled) (Journal of Human Sciences, 2022)
In the name of of Allah the Merciful. Praise be to God, Lord of the Worlds, and prayers and peace be upon the most honorable messengers, our Prophet Muhammad and all his family and companions. As for selling: This is a simple research, in which I tried to collect the most important reasons for the conflict of jurisprudential narrations that we received from Imam Malik. After knowing the contradiction, and knowing the narrations in language and terminology, I mentioned that there are seven main reasons for the conflicting narrations from Imam Malik, including: The difference of Maliki scholars in the adoption of some assets, including the change in the jurisprudence of Imam Malik, and sometimes this is because the hadith of Imam Malik - may God have mercy on him - did not reach. It may be due to a difference in a form, or a letter, or a word that was transmitted from the imam, or because of a mistake or delusion from those who narrated from the imam or without them. This may be due to lying about the imam, and the contradiction may be due to the disagreement of the Malikis in understanding the words of Imam Malik - may God have mercy on him. Then I mentioned a conclusion in which the most important findings of the research thanks God first and last